(3GdHfhc GdGSdGejI GdOhdjI h YbhOgG eY GTGQI NGUI dfXGe GdJCLjQ GdJehjdj (B/s - (3NGdO, gTGes ((3GdGScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2007)
1) (3GdJYQja HGdHfhc GdGSdGejI GdOhdjI h YbhOgG (B: (3GdeTGQcI aj QCS eGd GdeTQhYGJ GdefJLI , GdbQhV Ohf aGFOI , GdHjY HGdGLd , GdJehjd Yf WQjb GdeTGQcI aj GdahGFO(B2) (3GdJCLjQ GdJehjdj aj fWGb GdHfhc GdeYfjI (B: (3eGgjI GdJCLjQ GdJehjdj h CWQGag h YfGUQ fXGe GdJCLjQ GdJehjdj (B.s
Keywords: (3GdHfhcs; (3GdHfhc GdGSdGejIs; (3GdJehjds